The role of the university in the development of cooperative solidarity organizations - Montañez Moya, Gloria Silviana (Cooperativismo & Desarrollo, 2017)
Purpose: Solidary entrepreneurship represents one of the bases of progress in today’s society. Therefore, the objectives of this article are to identify the perception of university students about the desirability, viability and intentionality of creating their own companies, as well as the motivations to generate a cooperative society and to evaluate the role of the university in the promotion of business activity. Description: Topics are presented independently to sensitize the reader about the importance of cooperative entrepreneurial education. Point of view: It is considered pertinent to trigger a reflection in university life that allows, among other things, to visualize the benefits generated by cooperatives in the welfare of society. Conclusions: The desire and intention of immediate future graduates towards company creation, and its’ constitution under the legal form of cooperative societies, in order to favor their viability, exists.